Pengaruh Mutu Pelayanan Kesehatan Terhadap Tingkat Kepuasan Peserta JKN di Puskesmas Oesapa Tahun 2022 - Dominika Priska Tsu; Tadeus A.L. Regaletha; Yoseph Kenjam (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Patient satisfaction is one of the important elements to measure the health services quality. This is so that health care facilities can remain standing and continue to grow in providing health service to the community. National health insurance is a government program that aims to provide health insurance for all Indonesian people. The purpose of the research was to determine the effect of the health services quality on the satisfaction level of participants in the national health insurance at the Oesapa Public Health Center. This type of research is quantitative research using cross sectional research design. The total population is 833 who are participants of the national health insurance. The number of samples is 138 with the sampling technique is purposive sampling. Data collection was done bye interview using a questionnaire. The statistical test used is simple linear regression analysis. The result of the research indicate that there is a significant influence between the health services quality in the dimension of tangible (p value = 0,000), reliability (p value = 0,000), responsiveness (p value = 0,000), assurance (p value = 0,000) and empathy (p value = 0,000) for the level of satisfaction of national health insurance at the Oesapa Public Health Center in 2022. It is recommended for Oesapa Public Health Center to maintain the health services quality so that it remains good and continues developed so that patients who use health facilities are satisfied with the quality of services provided.